(untitled) (Scientific journal of the Fergana State University, 2023)
This article describes the historical and legal processes of the housing issue in Uzbekistan and the foundations of state regulation of relations. The need for housing is one of the most pressing problems: it is universal and affects all segments of the population. It is an irreplaceable, stable and constantly growing need. The possession of housing is important for the usual, normal way of life in society, for the formation of man as a person, for security. The article also presents conceptual views on the practice of organizing the housing stock management system in Uzbekistan and the prospects for the development of the sector.